2019
DOI: 10.1136/bjophthalmol-2018-313200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aspects of idiopathic paediatric uveitis and juvenile idiopathic arthritis associated uveitis in Chinese Han

Abstract: BackgroundIdiopathic paediatric uveitis (IPU) and juvenile idiopathic arthritis associated uveitis (JIA-U) are the two most common entities in paediatric uveitis. This study addressed the possible association of IPU and JIA-U with genes that had been shown earlier to be associated with juvenile idiopathic arthritis.MethodsWe carried out a case-control association study involving 286 IPU, 134 JIA-U patients and 743 healthy individuals. A total of 84 candidate single nucleotide polymorphisms (SNPs) in 60 genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Recent studies have reported that PSMA3 can act as a negative regulator by degrading the early response gene 1 product in gut-associated inflammation [9]. In addition, PSMA3/rs2348071 was identified as a single nucleotide polymorphism associated with juvenile idiopathic arthritis-associated uveitis based on data from studies conducted in the Chinese Han population [10]. Furthermore, several studies have demonstrated the abnormal expression profiles of PSMA3 in several cancers and identified PSMA3 as a cancer-related indicator [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that PSMA3 can act as a negative regulator by degrading the early response gene 1 product in gut-associated inflammation [9]. In addition, PSMA3/rs2348071 was identified as a single nucleotide polymorphism associated with juvenile idiopathic arthritis-associated uveitis based on data from studies conducted in the Chinese Han population [10]. Furthermore, several studies have demonstrated the abnormal expression profiles of PSMA3 in several cancers and identified PSMA3 as a cancer-related indicator [11].…”
Section: Introductionmentioning
confidence: 99%